Analisis Pengukuran Kinerja Perusahaan Dengan Menggunakan Pendekatan Balanced Scorecard Pada Famous Bridal Art Collection Kota Probolinggo - Seger Priantono (Ecobuss, 2016)
This research was conducted at the Famous Bridal Art collcetion in Kota Probolinggo with research objects such as Corporate Performance Measurement Analysis Using Balanced Scorecard Approach. This is done with the aim of analyzing the measurement of company performance with the balanced scorecard pendeketan Bridal Famous Art Collection in Kota Probolinggo, for the researchers to formulate the problem "How is the analysis of corporate performance measurement balanced scorecard approach at Bridal Famous Art Collection in Kota Probolinggo?" This type of research is descriptive quantitative research. Variables used in this research is a financial perspective, customer perspective, internal business processes, learning and growth perspective. The population used the financial statements of the sampled financial statements Year 2012-2014. Data analysis method used method of financial perspective, customer perspective, internal business processes, learning and growth perspective as well as the validity of the test. Results of the study financial perspective there are weaknesses due to the improvement and deterioration every year. Customer perspective has been as expected, it can be seen from the increasing number of customers each year. Perpsektif internal business processes demonstrate a good thing for the process of innovation and operations. Perpspektif learning and growth obtained from questionnaires so that employees can be considered satisfied. From four perspectives can be judged that the performance measures Famous Art Collection Bridal good enough. Keywords : Corporate perfomance, Balanced Scorecard